Assessment of the efficacy of MRI for detection of changes in bone morphology in a mouse model of bone injury. Issue 1 (2nd November 2012) - Taha, May A.; Manske, Sarah L.; Kristensen, Erika; Taiani, Jaymi T.; Krawetz, Roman; Wu, Ying; Ponjevic, Dragana; Matyas, John R.; Boyd, Steven K.; Rancourt, Derrick E.; Dunn, Jeff F.
<x xml:space="preserve">Abstract</x> Purpose To determine whether magnetic resonance imaging (MRI) could be used to track changes in skeletal morphology during bone healing using high‐resolution micro‐computed tomography (μCT) as a standard. We used a mouse model of bone injury to compare μCT with MRI. Materials and Methods Surgery was performed to induce a burr hole fracture in the mouse tibia. A selection of biomaterials was immediately implanted into the fractures. First we optimized the imaging sequences by testing different MRI pulse sequences. Then changes in bone morphology over the course of fracture repair were assessed using in vivo MRI and μCT. Histology was performed to validate the imaging outcomes. Results The rapid acquisition with relaxation enhancement (RARE) sequence provided sufficient contrast between bone and the surrounding tissues to clearly reveal the fracture. It allowed detection of the fracture clearly 1 and 14 days postsurgery and revealed soft tissue changes that were not clear on μCT. In MRI and μCT the fracture was seen at day 1 and partial healing was detected at day 14. Conclusion The RARE sequence was the most suitable for MRI bone imaging. It enabled the detection of hard and even soft tissue changes. These findings suggest that MRI could be an effective imaging modality for assessing changes in bone morphology and pathobiology. J. Magn. Reson. Imaging 2013;38:231–237. © 2012 Wiley Periodicals, Inc.